Anticoagulant activity of krait, coral snake, and cobra neurotoxic venoms with diverse proteomes are inhibited by carbon monoxide. Issue 8 (December 2019) - Nielsen, Vance G.; Frank, Nathaniel; Turchioe, Brian J.
Abstract : Background: A phenomena of interest is the in vitro anticoagulant effects of neurotoxins found in elapid venoms that kill by paralysis. These enzymes include phospholipase A2 (PLA2 ), and it has recently been demonstrated that carbon monoxide inhibits the PLA2 -dependent neurotoxin contained in Mojave rattlesnake type A venom. The purpose of this investigation was to assess if the anticoagulant activity of elapid venoms containing PLA2 and/or three finger toxins could be inhibited by carbon monoxide. Methods: Venoms collected from Bungarus multicinctus, Micrurus fulvius, and five Naja species were exposed to carbon monoxide via carbon monoxide releasing molecule-2 prior to placement into human plasma. Coagulation kinetics were assessed via thrombelastography. Results: Compared with plasma without venom addition, all venoms had significant anticoagulant effects, with a 160-fold range of concentrations having similar anticoagulant effects in a species-specific manner. Carbon monoxide significantly inhibited the anticoagulant effect of all venoms tested, but inhibition was not complete in all cases. Conclusion: Given that individual neurotoxin activity often depends on intact activity that includes anticoagulant action, it may be possible that carbon monoxide inhibits neurotoxicity. Future investigation is justified to assess such carbon monoxide mediated inhibition with purified neurotoxins in vitro and in vivo .